2018
DOI: 10.1111/ijpo.12474
|View full text |Cite
|
Sign up to set email alerts
|

A mixed methods analysis of maternal response to children's consumption of a palatable food: differences by child weight status

Abstract: Summary Background Little is known about how mothers respond to their child eating palatable foods. Objectives The objectives of the study are to examine maternal behaviours when children are presented with a large portion of energy‐dense palatable food in an experimental setting and to examine differences by child weight status. Methods Mother–child dyads (N = 37) (mean child age 70.8 months) participated in a videotaped eating protocol with cupcakes. Anthropometrics were measured. Videos were analysed using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 28 publications
0
1
0
Order By: Relevance
“…Aligned with previous studies, regardless of their BMI, most children showed a preference for sweetened beverages, instantaneous noodles, package chips, salty crackers, stuffed biscuits, and sweets. 21 The consumption of these foods is closely related to the onset of obesity. In the present study, irrespective of their nutritional status, 70% of children had meals while viewing television, while on a computer, or when using a cell phone.…”
Section: Discussionmentioning
confidence: 99%
“…Aligned with previous studies, regardless of their BMI, most children showed a preference for sweetened beverages, instantaneous noodles, package chips, salty crackers, stuffed biscuits, and sweets. 21 The consumption of these foods is closely related to the onset of obesity. In the present study, irrespective of their nutritional status, 70% of children had meals while viewing television, while on a computer, or when using a cell phone.…”
Section: Discussionmentioning
confidence: 99%
“…However, as they enter the preschool age range, parental concern about children's overeating increases (Pesch et al 2016a), and parents can sometime begin to express hostility toward their child's overeating. Parents sometimes begin to express frustration with attempts to restrict the child's eating and may begin to distance themselves from the child as they begin to experience growing societal disapproval of their child's overeating (Pesch et al 2019b).…”
Section: Parental Feeding Behaviorsmentioning
confidence: 99%